KECEMASAN DAN INSOMNIA PADA MASA MENOPAUSE - Endah Puji Astuti (MEDIA ILMU KESEHATAN, 2012)
Background: The climacterium is often regarded as a sign or signal that a person has begun to aging when this period is marked by physical and psychological setbacks. Psychological changes that occur during menopause can lead to different attitudes, among which is the existence of a crisis manifested in psychological symptoms such as depression, irritability, suspicion, a lot of anxiety and insomnia, as the person is very confused and restless. Insomnia is a state when one cannot sleep or has disruption of sleep patterns. The person concerned may not be able to sleep, difficult to sleep or wake up easily and then cannot sleep anymore. Sleeping trouble (insomnia) is a health problem that is very disturbing and should be anticipated in menopausal women. Objective: To determine the relationship of anxiety levels to the occurrence of insomnia in menopausal women at BPS (privately practicing midwife) Seri Suprapti in Purworedjo. Methods: This study used a descriptive correlational design with a cross sectional approach. Sampling used total sampling as many as 95 people who had been menopause. Data collection used questionnaires. Analysis of the data used Chi-Square test. Results: The majority of menopausal women had moderate levels of anxiety (72.5%) and insomnia (62.5%). From the statistical test, it prevailed significant relationship between anxiety and insomnia in menopause, with p = 0.03 (p <0,05). Conclusion: Menopausal women who had a high level of anxiety had a risk of insomnia than women with low levels of anxiety. Menopausal women are expected to actively search for information related to the changes in menopause. Sufficient understanding of the changes in menopause can help reduce anxiety. Keywords: Menopause, anxiety, insomnia